Optimalisasi Layanan Bengkel Melalui Metode PDCA: Studi Kasus Peningkatan Efisiensi Super Cepat Service di PT ABC Sunter - Agung, Kurniawan; Rosalinda, Rosalinda; Wismantoro, Sindhu; Indriyati K, Retno; Hutasoit, Jisman (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
PT ABC, an official workshop leading in automotive service and repair, introduced the Super-Fast Service (SSC) service to meet the needs of customers who want regular maintenance of their vehicles quickly and reliably. However, the increasing demand for SSC services at PT ABC Sunter creates challenges in maintaining service quality and efficiency, as seen from the decline in Customer Satisfaction Index (CSI) scores in the "Q13" time metric at the beginning of 2020. This research aims to identify and overcome problems -the problem through a PDCA (Plan-Do-Check-Act) approach, which includes restructuring work processes, intensive training for employees, and increasing resources to handle the increase in vehicle volume. At the planning stage, fishbone analysis identifies causal factors such as suboptimal work processes, lack of employee training, increasing vehicle volume without adjusting capacity, and long waiting times for customers. Implementation of improvement ideas is carried out by testing work process restructuring and intensive training. The evaluation results show a significant reduction in average waiting time from 60 minutes to 30 minutes, an increase in customer satisfaction from 75% to 85%, an increase in employee skills from 80% to 90%, and an increase in service capacity from 80 vehicles per day to 100 vehicles per day. day. In the action stage, the results of effective improvements are documented and become new operating standards, including the creation of new SOPs, ongoing training programs, additional resources as needed, and continuous monitoring of service times and customer satisfaction. The implementation of the PDCA method succeeded in increasing the efficiency of SSC services at PT ABC Sunter, showing the importance of a systematic and sustainable approach in improving service quality in the automotive industry.